Relationship between antioxidant potential and oxidative damage to lipids, proteins and DNA in aged rats - Sivoňová, Monika; Tatarková, Zuzana; Ďuračková, Zdeňka; Dobrota, Dušan; Lehotský, Ján; Matáková, Tatiana; Kaplán, Peter (Physiological research, 2007)
Oxidative stress has been implicated to play a major role in aging and age-related diseases. In the present study, we investigated the effects of aging on the total antioxidant capacity, uric acid, lipid peroxidation, total sulfhydryl group content and damage to DNA in adult (6 months), old (15 months) and senescent (26 months) male Wistar rats. The antioxidant capacity, determined by phycoerythrin-based TRAP method (total peroxyl radical-trapping potential) was significantly decreased in the plasma and myocardium of old and senescent rats, whereas plasma level of uric acid was elevated in 26-month-old rats. Age-related decline in plasma and heart antioxidant capacity was accompanied by a significant loss in total sulfhydryl group content, increased lipid peroxidation and higher DNA damage in lymphocytes. Correlations between TRAP and oxidative damage to lipids, proteins and DNA suggest that the decline in antioxidant status may play an important role in age-related accumulation of cell damage caused by reactive oxygen species.
Keywords: financování organizované; kyselina močová; Antioxidants; Rats, Wistar; oxidační stres; Aging; Oxidative Stress; sulfhydrylové sloučeniny; Reactive Oxygen Species; peroxidace lipidů; Financing, Organized; Lipid Peroxidation; Comet Assay; antioxidancia; stárnutí; Sulfhydryl Compounds; reaktivní formy kyslíku; kometový test; Uric Acid; potkani Wistar